Comparative constitutional history. Volume 1 : principles, developments, challenges - Biagi, Francesco; Frosini, Justin Orlando; Mazzone, Jason, 1970- (Leiden ; Boston : Brill, 2020)
"While comparative constitutional law is a well-established field, less attention has been paid so far to the comparative dimension of constitutional history. The present volume, edited by Francesco Biagi, Justin O. Frosini and Jason Mazzone, aims to address this shortcoming by bringing focus to comparative constitutional history, which holds considerable promise for engaging and innovative work along several key avenues of inquiry. The essays contained in this volume focus on the origins and design of constitutional governments and the sources that have impacted the ways in which constitutional systems began and developed, the evolution of the principle of separation of powers among branches of government, as well as the origins, role and function of constitutional and supreme courts. Contributors include: Mark Somos, Gohar Karapetian, Justin O. Frosini, Viktoriia Lapa, Miguel Manero de Lemos, Francesco Biagi, Ctherine Andrews, Gonçalo de Almeida Ribeiro, Mario Alberto Cajas-Sarria, and Fabian Duessel."
George Bancroft in Göttingen: an American Reception of German Legal Thought / Mark Somos -- Uniformity and Diversity: a Confrontation between French and Dutch Thought on Citizenship / Gohar Karapetian -- The Historical and Legal Significance of Constitutional Preambles: a Case Study on the Ukrainian Constitution of 1996 / Justin O. Frosini and Viktoria Lapa -- Why the Court of Final Appeal of Hong Kong Should Re-Assert Its Power to Review Acts of the Standing Committee / Miguel Manero de Lemos -- The Separation of Powers and Forms of Government in the MENA Region Following the 'Arab Spring': a Break with the Past? / Francesco Biagi -- 'The Constitution Will Be Our Last Hope in the Monetary Storm.' Institutions of Constitutional Protection and Oversight in Mexico and Their Contribution to Atlantic Constitutional Thought (1821-1841) / Catherine Andrews -- Judicial Review of Legislation in Portugal: Genealogy and Critique / Gonçalo de Almeida Ribeiro -- Defending the Judiciary? Judicial Review of Constitutional Amendments on the Judiciary in Colombia / Mario Alberto Cajas-Sarria -- Direct Individual Access to Constitutional Justice in South Korea and Taiwan / Fabian Duessel.
Includes bibliographical references and index.
Online resource; title from PDF title page (Brill, viewed on March 3, 2021).
eBooks on EBSCOhost
Keywords: Constitutional law; Constitutional history; Separation of powers; Constitutional courts; Federal government; Droit constitutionnel; Histoire constitutionnelle; Séparation des pouvoirs; Cours constitutionnelles; Constitutional courts; Constitutional history; Constitutional law; Federal government; Separation of powers